Proteome dataset of Candida albicans (ATCC10231) opaque cell - Zore, Gajanan; Abdulghani, Mazen; Kodgire, Santosh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra (BMC Research Notes, 2024)
<h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 0px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Objectives Candida albicans, a polymorphic yeast, is one of the most common, opportunistic fungal pathogens of humans. Among the different morphological forms, opaque form is one of the least-studied ones. This opaque phenotype is essential for mating and is also reported to be involved in colonizing the gastrointestinal tract. Considering the significance of the clinical and sexual reproduction of C. albicans, we have investigated the morphophysiological modulations in opaque form using a proteomic approach. <h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 24px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Data description In the current investigation, we have used Micro-Liquid Chromatography-Mass Spectrometry (LC-MS/MS) analysis to create a protein profile for opaque-specific proteins. Whole-cell proteins from C. albicans (ATCC10231) cells that had been cultured for seven days on synthetic complete dextrose (SCD) medium in both as an opaque (test) and as a white (control) form cells were extracted, digested, and identified using LC-MS/MS. This information is meant to serve the scientific community and represents the proteome profile (SWATH Spectral Libraries) of C. albicans opaque form.